2015
DOI: 10.4103/0972-6748.160950
|View full text |Cite
|
Sign up to set email alerts
|

Delusional parasitosis with folie à deux: A case series

Abstract: Delusional parasitosis (DP) is characterized by single hypochondriacal delusion in which patient feels he/she is infested with insects. The authors present a case series of three cases of DP with shared psychotic disorder (folie à deux) in which one individual developed a delusional belief in the context of a close relationship with another person or people who already had an established delusional idea. All patients of DP were assessed in the outpatient department of Psychiatry of a tertiary care hospital. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In a case series of three DP patients started on risperidone 2mg/day increased upto 4–6mg, good improvement was seen within 3 months. [ 11 ] In another study on DP, a good response was reported in three patients with olanzapine at a dose of 5mg/day increased to 10 mg.[ 12 ] Aripiprazole, considered as a “third-generation antipsychotic,” has also been tried in DP in the dose of 5–10 mg/day. [ 13 ] One distinct advantage of aripiprazole over other SGAs is the absence of weight gain.…”
Section: Antipsychoticsmentioning
confidence: 99%
“…In a case series of three DP patients started on risperidone 2mg/day increased upto 4–6mg, good improvement was seen within 3 months. [ 11 ] In another study on DP, a good response was reported in three patients with olanzapine at a dose of 5mg/day increased to 10 mg.[ 12 ] Aripiprazole, considered as a “third-generation antipsychotic,” has also been tried in DP in the dose of 5–10 mg/day. [ 13 ] One distinct advantage of aripiprazole over other SGAs is the absence of weight gain.…”
Section: Antipsychoticsmentioning
confidence: 99%
“…Psychogenic pruritus is considered psychiatric in origin and presents as itch in conditions such as obsessive-compulsive disorders, depression, and delusions of parasitosis [ 10 , 11 ]. It is characterized as an excessive impulse to scratch or pick at normal skin.…”
Section: Itch In Primarily Noninflammatory Diseasesmentioning
confidence: 99%
“…Shared delusional infestation is estimated to occur in approximately 5–15% of cases [ 24 ]. In folie à deux , two individuals may concomitantly share a diagnosis of delusional infestation [ 25 ]. Cases of three or more concomitant patients with delusional infestation have been reported.…”
Section: Clinical Considerationsmentioning
confidence: 99%